A new road to cancer-drug resistance. (22nd November 2018) - Schlacher, Katharina
The discovery of a mechanism that leads to cancer-therapy resistance highlights the many ways that tumour cells can adapt to survive — and reveals the limitations of categorizing patients by their gene mutations. An unexpected survival strategy for tumour cells.